Don't gloat about goats - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Goat production handbook Published by the Ministry of Agriculture of Jamaica and the Goat Breeders Society of Jamaica, with support from CARDI, 2002. 60 pp. US$ 10 (Jamaica) US$ 12 (rest of the Caribbean) US$ 15 Euro 14.55 (rest of the world)